PENINGKATAN KEMAMPUAN LITERASI DIGITAL BAGI GURU MELALUI E-MODUL - Siti Nurhalijah; Icha Dwi Indriani; Nabila Aulia Putri; Dinda Mutia; Meizi Fadhilah Saragih; Aderamadani; Nur Annisa Putri Sinaga; Yurmadina Fitri Daulay; Lisa Septia Dewi Br.Ginting (JURNAL ILMIAH NUSANTARA, 2025)
Referring to the four competencies that must be possessed in the 21st century, digital literacy skills are one of the most important competencies for today's young generation, especially teachers. The purpose of this study is to improve teachers' digital literacy skills. Learning that occurs in partner schools is usually dominated by the role of teachers and pays less attention to the development of students' potential and character. Teachers face challenges in providing additional learning to students who have not yet achieved full understanding in their lessons. Many teachers are not yet proficient in using digital literacy. The solution offered in solving the priority problems of partners is through holding training to design interactive e-learning modules using information technology. Students who have not completed their learning can use interactive e-modules to study independently at home. Interactive learning e-modules are not only useful for remedial learning, but are also effective for use in both group and individual learning in the classroom. This activity involves the use of presentation methods, discussions, and practical exercises in creating interactive e-modules. Training participants are asked to fill out a questionnaire at the beginning of the session to evaluate their knowledge of information technology-based teaching materials before the activity begins. After that, participants will receive intensive training and assistance in the process of creating interactive learning e-modules using information technology. It is expected that the results of this training and mentoring will improve teacher skills in developing teacher digital literacy skills.